Lncrna mort (Znf667-as1) in cancer—is there a possible role in gynecological malignancies? - Di Fiore, Riccardo (2021)
Funding Information: The publication of this manuscript was funded by the European Cooperation in Science & Technology program (EU COST)?COST Action CA18117: GYNOCARE-?European Network for Gynaecological Rare Cancer Research: From Concept to Cure.? R.D.F., S.S., S.A.O., J.J.O, M.P.W., J.B., A.Y., M.V.-S., Y.S., A.G., and J.C.-A. are Action management committee members and/or form part of Working Groups 1?3, and J.C.-A. is the chairperson of this Action. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.